2020
DOI: 10.1007/s00271-020-00701-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrating thermal stress indexes within Shuttleworth–Wallace model for evapotranspiration mapping over a complex surface

Abstract: The main goal of this work was to evaluate the potential of the Shuttleworth-Wallace (SW) model for mapping actual crop evapotranspiration (ET) over complex surface located in the foothill of the Atlas Mountain (Morocco). This model needs many input variables to compute soil (r s s ) and vegetation ( r v s ) resistances, which are often difficult to estimate at large scale particularly soil moisture. In this study, a new approach to spatialize r s s and r v s based on two thermal-based proxy variables was prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…The closure error is close to 10 % for both field which is in the acceptable ranges (from 10% to 30%) reported in Twine et al (2000). The obtained results are relatively good and the closure of the energy balance is relatively well verified in comparison with other studies (Elfarkh et al, 2021;Testi et al, 2004;Twine et al, 2000). To correct some small uncertainties of non-closure of the energy balance, the Bowen ratio was used to recompute H and LE by forcing the energy balance closure with the measured values of Bowen ratio.…”
Section: Eddy Covariance Stationssupporting
confidence: 54%
See 1 more Smart Citation
“…The closure error is close to 10 % for both field which is in the acceptable ranges (from 10% to 30%) reported in Twine et al (2000). The obtained results are relatively good and the closure of the energy balance is relatively well verified in comparison with other studies (Elfarkh et al, 2021;Testi et al, 2004;Twine et al, 2000). To correct some small uncertainties of non-closure of the energy balance, the Bowen ratio was used to recompute H and LE by forcing the energy balance closure with the measured values of Bowen ratio.…”
Section: Eddy Covariance Stationssupporting
confidence: 54%
“…cropped in conditions without any stress conditions and may be estimated with models while under field conditions actual ET is estimated with models because crops are generally subject to water (and/or other stress conditions). Some of these models use remotely sensed data such as surface albedo, Leaf Area Index (LAI), Normalized Difference Vegetation Index (NDVI), Land Surface Temperature (LST) (Allen et al, 2011;Granger, 2000;Kharrou et al, 2013;Kustas and Norman, 1996;Li et al, 2009) and soil moisture (Elfarkh et al, 2021;Gokmen et al, 2012;Walker et al, 2019). ETc act component can be predicted based on water balance at a daily time scale.…”
Section: Introductionmentioning
confidence: 99%
“…Second, rsmin was fixed throughout the year in the SW model, regardless of seasonal variations of this parameter with environmental and vegetation conditions (Winkel et al, 2001;Wever et al, 2002;Douglas et 500 al., 2009). Therefore, no consideration of seasonal cycle of rsmin may impact the quality of the PET product (Hu et al, 2009;Zhu et al, 2013;Elfarkh et al, 2021). For instance, Hu et al (2009) and Zhu et al (2013) found that ET was systematically overestimated or underestimated using the SW model with fixed parameters.…”
Section: Uncertainties In Parameterizations Of the Sw Modelmentioning
confidence: 99%
“…Second, r smin was fixed throughout the year in the SW model, regardless of seasonal variations of this parameter with environmental and vegetation conditions (Winkel et al, 2001;Wever et al, 2002;Douglas et al, 2009). Therefore, no consideration of the seasonal cycle of r smin may impact the quality of the PET product (Hu et al, 2009;Zhu et al, 2013;Elfarkh et al, 2021). For instance, Hu et al (2009) and Zhu et al (2013) found that ET was systematically overestimated or underestimated using the SW model with fixed parameters.…”
Section: Uncertainties In Parameterizations Of the Sw Modelmentioning
confidence: 99%
“…In order to reduce the impacts of the non-closure of the energy balance in the EC system (Wilson et al, 2002;Foken, 2008), we used the corrected half-hourly or hourly EC LE and H observations and only retained daytime records with a Bowen ratio between 0.90 and 1.10 to calibrate the SW model. Although such processing could reduce uncertainties, the energy imbalance was not fully solved in our study and may lead to inevitable errors in the calibrated parameter of r smin and therefore the global PET estimates (Hu et al, 2009;Elfarkh et al, 2021;Chen et al, 2022). In this study, to maximize the use of data, the MSD method was employed to fill the gaps in the EC LE measurements.…”
Section: Uncertainties In Datasets For Calibrating and Driving The Sw...mentioning
confidence: 99%